Investigating the interrelationships among various measures of family strengths - Wheeler, Tony (Kansas State University, 2008)
The study of family strengths, as opposed to family dysfunction, has increased over the past few decades. Six interrelated components of family strength were identified that may affect the degree of marital satisfaction of husbands and wives. The six components - worth, commitment to relationship stability, commitment to relationship growth, communication, positive interaction, and time spent together - are characteristics within a family that may have substantial connections. Identical surveys were administered to couples in three major metropolitan areas. The data for the study were a sub-sample of data collected as a mail survey as part of a larger survey of membership retention within a mainline Protestant denomination. The main mail survey contained 10 pages. For about one-third of the sample, an additional two-page survey was given concerning premarital counseling and marital satisfaction. Another third of the sample was given an additional 2-page survey on family strengths and marital satisfaction. In addition to 20 family strengths items, those surveyed were asked to respond to the three questions of the Kansas Marital Satisfaction Scale. Data from these couples were used to test a hypothesized model of the interrelationships between the various measures of family strength using a detailed path analysis model with marital satisfaction as the dependent variable. The variables worth, commitment, communication, positive interaction, and time together functioned as intervening variables in the model with age, gender, various measures of religiosity, income, education, and age of children functioning as independent variables. The data were then analyzed by ordinary least squares regression techniques to test the model using marital satisfaction as the dependent variable. The results of testing the model indicated that strength in certain characteristics predicted strength in other characteristics at statistically significant levels (p < .05). Intrinsic religiosity predicted worth. Worth predicted commitment to stability and commitment to growth. The two areas of commitment predicted communication. Communication predicted positive interaction. Positive interaction predicted time together, and strengths in most of the characteristics predicted marital satisfaction. It is important for researchers, educators, therapists, and other professionals who work with families to gain an understanding and awareness of the current breakdown of marriage and family in our Western society. A greater understanding of family strengths and how they work together is crucial to providing families and family professionals with information useful for supporting family systems.
Keywords: marriage; strong families; Sociology, Individual and Family Studies (0628)